2010
DOI: 10.1021/nn1015665
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Extraction of Ultrathin Inner Shells from Double-Wall Carbon Nanotubes

Abstract: We present an efficient method to extract inner shells of double-wall carbon nanotubes (DWCNTs) in liquid phase. The extraction of inner from outer shells is achieved by cutting the DWCNTs with vigorous sonication in water containing surfactants. The extracted shells are perfectly isolated single-wall carbon nanotubes (SWCNTs) and can be separated using density gradient ultracentrifugation. Statistical analysis using high-resolution transmission electron microscopy reveals that the enrichment of SWCNTs with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 31 publications
8
49
1
Order By: Relevance
“…[ 5 ] A similar observation of overlapping inner and outer tube contributions was also reported by Miyata et al who extracted the inner tubes. [ 33 ] Since the diameter distribution for their samples was similar as it is in this work, such overlaps can also be expected. Figure 2 b shows the normalized (normalization procedure described in the Experimental Section) absorption spectra for E 11 transitions of the pristine, not-fi lled DWCNT sample and two differently fi lled DWCNT samples: the DWCNT annealed at 1460 °C that inhibit the highest number of the longest chains and the DWCNT annealed at 1400 °C, as these showed the greatest change in absorption features compared to the pristine sample.…”
Section: Optical Absorption Of the Differently Treated Dwcnt Samplessupporting
confidence: 67%
See 1 more Smart Citation
“…[ 5 ] A similar observation of overlapping inner and outer tube contributions was also reported by Miyata et al who extracted the inner tubes. [ 33 ] Since the diameter distribution for their samples was similar as it is in this work, such overlaps can also be expected. Figure 2 b shows the normalized (normalization procedure described in the Experimental Section) absorption spectra for E 11 transitions of the pristine, not-fi lled DWCNT sample and two differently fi lled DWCNT samples: the DWCNT annealed at 1460 °C that inhibit the highest number of the longest chains and the DWCNT annealed at 1400 °C, as these showed the greatest change in absorption features compared to the pristine sample.…”
Section: Optical Absorption Of the Differently Treated Dwcnt Samplessupporting
confidence: 67%
“…[ 32 ] Features of the excitonic transitions between corresponding van Hove singularities of DWCNT are strongly attenuated in comparison to SWCNT. [ 12,14,33,34 ] On the one hand, a decrease in absorption features is often a result of carrier/hole doping to the carbon nanotube as observed for SWCNT. [35][36][37][38] As mentioned earlier, Zólyomi et al found that a charge transfer from outer to inner tube is taking place.…”
Section: Optical Absorption Of the Differently Treated Dwcnt Samplesmentioning
confidence: 99%
“…They were first filled into the centre cavity of a parent tube, followed by a 1,200 °C-annealing to induce transformation. These newly formed inner tubes were subsequently extracted using ultrasonication8 and further separated from the outer tube templates by density gradient ultracentrifugation (DGU)1112 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…By carefully choosing the polycyclic aromatic hydrocarbon precursors, one can, therefore, foresee a controllable tuning of the different chiralities synthesized. With the inner-shell extraction technique developed recently8, precise verification of the CNTs synthesized is also possible through photoluminescence (PL) measurements9.…”
mentioning
confidence: 99%
“…S2). The chirality assignment is based on a report about the optical properties of the SWNTs with small diameters23. Based on the in situ PL spectral change as well as analysis using the Nernst equation, we determined the E red , E ox and E F of the (5,4)SWNTs to be −0.59, 0.75 and 0.08 V vs .…”
Section: Resultsmentioning
confidence: 99%